ANALISIS FAKTOR EKSPLOITASI BEBERAPA JENIS DIPTEROCARP DI IUPHHK-HA PT. BINA MULTI ALAM LESTARI PROVINSI KALIMANTAN TENGAH - Bambang Wira Adi Saputra; Udiansyah Udiansyah; Suyanto Suyanto (Jurnal Sylva Scienteae, 2023)
One of the most influential indicators in harvesting forest products is the exploitation of the resulting value. Based on the Decree of the Ministry of Environment and Forestry, the value set for the exploitation factor is 0.70. The method used to measure the exploitation factor is using the “Smalian” formula from Moeljono. SB Aspects of utilization factors and volume of branch-free logs are used as primary data and secondary data as additional value for exploitation factor data obtained from the company. The secondary data of this research is based on general conditions that occur in the field, topography, area and location of the study as well as the location of the cutting plots. At PT Bina Multi Alam Lestari, the exploitation factor value is obtained with an average volume of 10.24 m free branching logs and an average of 11.77 m branch free logs which may be exploited up to 10 logs yards (logpond) are not deducted and depreciated. The value obtained is 0.87 which has entered the exploitation factor standard set by the government. While the yield and total value of the exploitation factor on average from flat slopes (0-8%) with exploitation factor values of 0.89 m, on steep slopes (8-15%) the average value is 0.89 m, and on steep slopes (8-15%) the average value is 0.89 m, and on steep slopes a bit steep. slopes (15-25%) the average value is 0.85 m and on steep slopes (25-45%) the average value of the exploitation factor is 0.85 m. While the average value of the exploitation factor based on the type of vegetation is obtained with the exploitation factor value of 0.87 m³.Salah satu indikator yang sangat berpengaruh dalam pemanenan hasil hutan adalah faktor eksploitasi nilai yang dihasilkan. Berdasarkan SK Kementerian Lingkungan Hidup dan Kehutanan nilai ketetapan yang ditetapkan untuk faktor eksploitasi sebanyak 0,70. Metode yang dipakai untuk mengukur faktor eksploitasi yaitu menggunakan rumus “Smalian” dari Moeljono. S.B. Aspek faktor pemanfaatan dan volume kayu bulat bebas cabang menjadi data primer yang digunakan dan data sekunder sebagai nilai tambahan data faktor eksploitasi yang diperoleh dari perusahaan. Data sekunder penelitian ini didasarkan pada kondisi umum yang terjadi di lapangan, topografi, luas dan lokasi penelitian serta lokasi petak tebang. Pada PT Bina Multi Alam Lestari diperoleh nilai Faktor eksploitasi dengan volume rata-rata sebanyak 10,24 m log bercabang bebas dan rata-rata 11,77 m log bebas cabang yang mungkin dapat dimanfaatkan hingga log yard (logpond) tidak dikurangkan dan disusutkan. Nilai yang diperoleh sebanyak 0,87 dimana sudah memasuki standar faktor eksploitasi yang ditetapkan oleh pemerintah. Sedangkan hasil dan jumlah nilai faktor eksploitasi rata-rata dari lereng datar (0-8%) dengan nilai faktor eksploitasi 0,89 m, pada lereng curam (8-15%) nilai rata-ratanya adalah 0,89 m, dan pada lereng agak curam. lereng (15-25%) nilai rata-ratanya adalah 0,85 m dan pada lereng yang curam (25-45%) nilai rata-rata faktor eksploitasinya adalah 0,85 m. Sedangkan nilai rata-rata faktor eksploitasi berdasarkan jenis vegetasi diperoleh dengan nilai faktor eksploitasi sebesar 0,87 m³.